Faktor Motivasi Wisatawan Berkunjung Ke Gwk Sebagai Salah Satu Destinasi Wisata di Bali - Salma Karamy; Khoirotunnisa Nur Priyanti; Farrah Puspita; Vita Cecilia; Gagih Padini (Peneliti.net, 2023)
Tourism is a sector that plays a role in the regional development process by encouraging regional economic growth. Tourism plays an important role in driving economic activities, improving people's welfare and creating jobs. The island of Bali has a variety of diverse tourist attractions. One of them is Gianyar Regency which is famous for its arts and culture. The interest of tourists visiting a tourist destination is influenced not only by its attractiveness, but also by the motivation of tourists to travel. . Tourist motivation is an important factor in determining which tourist attractions to visit. Tourism motivation studies have shifted from seeing motivation as a short-term process to looking at travel behavior, placing more emphasis on the influence of motivation on psychological needs and long-term planning, and endogenous as a very important factor. such as self-actualization. The research method used is in the form of literature review research techniques by reviewing national and international journals.